Acoustic emission from a dislocation kink accelerated by an external force - E. Douka; B. Polyzos; A. Trochidis (Archives of Acoustics)
The emission of elastic waves from a dislocation kink accelerated by a constant external force is presented. The dynamics of the dislocation kink interacting with longitudinal acoustic waves is described by a sine-Gordon--d'Alembert system, i.e. a sine-Gordon equation nonlinearly coupled with the d'Alembert wave equation. Within the framework of this model, the evolution of velocity of the dislocation kink altered by the applied force is determined, allowing for mechanical couplings. The total energy radiated from the dislocation kink and its spectral composition is calculated numerically and analytically. Computer simulations are presented, which graphically illustrate the analytical considerations and model the acoustic radiation. Key words: acoustic emission, dislocations dynamics, nonlinear waves.